2008
DOI: 10.1002/app.28172
|View full text |Cite
|
Sign up to set email alerts
|

Cure‐reaction kinetics of amine‐blocked polyisocyanates with alcohol using hot‐stage Fourier transform infrared spectroscopy

Abstract: Cure reaction between a series of N-methylaniline-blocked polyisocyanates, based on 4,4 0 -methylenebis(phenyl isocyanate), poly(tetrahydrofuran) and several substituted N-methylanilines, and n-decanol has been studied. The solid-state isothermal cure reaction was carried out using hot-stage FTIR spectroscopy, in the temperature range of 125-1458C. The urea carbonyl absorption band of blocked polyisocyanate moiety was used to monitor the conversion of blocked polyisocyanate into polyurethane. Kinetic and therm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 11 publications
0
12
0
Order By: Relevance
“…On the other hand, elevated curing temperature and/or long curing time leads to poor properties and yellowing of the coating. 43,44 The advantages and disadvantages of this system are summarized in Table 2.…”
Section: Pu Powder Coatingsmentioning
confidence: 99%
“…On the other hand, elevated curing temperature and/or long curing time leads to poor properties and yellowing of the coating. 43,44 The advantages and disadvantages of this system are summarized in Table 2.…”
Section: Pu Powder Coatingsmentioning
confidence: 99%
“…It has been shown that structures of blocking agents and isocyanates equally have a strong influence on deblocking temperature (1,(15)(16)(17). Several compounds, having active hydrogen atom, have been reported as blocking agents, including phenols, oximes, amides, imides, imidazoles, amidines, pyrazoles, N-methyl anilines, and active methylene compounds (1,2,(15)(16)(17)(18)(19)(20)(21). It has been reported that substituent present in the blocking agent has a very strong influence on the deblocking temperature.…”
Section: Introductionmentioning
confidence: 99%
“…The cleavage and release of blocking group, at high temperature, yields again an isocyanate function which can react and lead to crosslinking of polymer. Various blocking groups are used industrially or studied by research groups [18][19][20][21][22][23][24][25]. However, the blocking of isocyanate suffers from many limitations: the moisture sensitivity of isocyanate function, the high toxicity of free isocyanates and the general drawback common at all system, the undesirable release of volatile blocking agents.…”
Section: Introductionmentioning
confidence: 99%